Preliminary study of the population and reproductive dynamics of Echinaster sepositus (Spinulosida: Echinasteridae) in Cala del Racó - López Casares, Daniel; Hernández Pérez, José Carlos; Tena Medialdea, José; García March, José Rafael (Revista de Biología Tropical, 2024)
Introduction: The red starfish (Echinaster sepositus) is one of the most common asteroid species in the Mediterranean Sea. However, information about their biology or their role in benthic communities is scarce. Objective: This study aims to provide new information on the ecology of this species through the temporal characterization of the population of E. sepositus in Cala del Racó (Alicante, Spain) and the in situ monitoring of its reproductive cycle. Methods: For this purpose, three study areas were established at different depths. For each of the recorded starfish, data about the size, the substrate on which it was found, the area, the depth and the sex in the case of observing the reproduction were collected. Results: A total of 19 samplings have been carried out throughout a year of study. In this way, it has been possible to observe that the density of individuals increases in the shallower zone during autumn and winter, when the temperature drops to 14.13 ºC, while it decreases in spring and summer when the temperature rises to 27.17 ºC. Those results are reversed in the deepest part of the study. The highest density of individuals (0.51 ind/m2) occurred in October. Arborescent photophilic algae and crustose coralline algae were the substrates with the highest number of E. sepositus recorded. Medium to large specimens are located preferably on crustose coralline algae or arborescent photophilic algae, while smaller individuals were mostly located on Posidonia oceanica. No specimens of E. sepositus were observed spawning. Conclusions: Data leads to assume that there is a migration of starfishes towards more superficial areas when the water is at colder temperature and towards deeper areas when the temperature increases. It is valued the possibility that there is a change in the nutritional needs of E. sepositus throughout its development. According to our observations, the future reproduction studies should be concentrated between late-summer and early-autumn.